2002
DOI: 10.1103/physrevlett.89.213902
|View full text |Cite
|
Sign up to set email alerts
|

A Metamaterial for Directive Emission

Abstract: In this paper we present the first results on emission in metamaterial. We show how the specific properties of metallic composite material can modify the emission of an embedded source. We show that under proper conditions the energy radiated by a source embedded in a slab of metamaterial will be concentrated in a narrow cone in the surrounding media. An experimental demonstration of this effect is given in the microwave domain, and the constructed antenna has a directivity equivalent to the best reported resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
671
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,138 publications
(686 citation statements)
references
References 16 publications
8
671
0
7
Order By: Relevance
“…As Pendry investigated the first negative refractive index perfect lens (i.e., double negative MTMs with simultaneously negative permittivity, permeability and negative index of refraction) in 2000 [17], it is possible to design a compact size and high directive antennas [18,19]. Furthermore, metamaterial structures composed of 3-D metal grid superstrates have been used to improve the directivity of the antennas [20,21]. It should be noted that the aperture size of the metamaterial superstrate is much bigger than the size of the patch which makes the antenna very bulky.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Pendry investigated the first negative refractive index perfect lens (i.e., double negative MTMs with simultaneously negative permittivity, permeability and negative index of refraction) in 2000 [17], it is possible to design a compact size and high directive antennas [18,19]. Furthermore, metamaterial structures composed of 3-D metal grid superstrates have been used to improve the directivity of the antennas [20,21]. It should be noted that the aperture size of the metamaterial superstrate is much bigger than the size of the patch which makes the antenna very bulky.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, a 2D single sided metasurface structure based on an electrically split ring resonator (eSRR) [26] is designed by choosing proper dimensionality and orientation such that it exhibits NRI property in the direction of the wave propagation, and hence it can be used to improve the directivity of the EM emission. This 2D metasurface structure has the advantage of easier fabrication and assembly processes over the volumetric MTMs (mentioned in [20][21][22]), so it can be scaled down to be fabricated for THz antennas for high resolution imaging and biomedical application (e.g., heart beat measurements). Secondly, a slotted waveguide antenna [27] is used as EM radiator instead of horn antenna or patch antenna because it is difficult to design a horn antenna with flared surfaces in the THz regime.…”
Section: Introductionmentioning
confidence: 99%
“…Use of the electromagnetic band-gap (EBG) and frequency selective surface (FSS) as a superstrate has been proposed by Pirhadi et al [5]. Also, use of metamaterials as antenna substrates has been proposed by Enoch et al [6] and Wu et al [7]. An interesting class of metamaterials (MTMs), known as the zero-index medium, exhibits a remarkable influence on wave propagation properties.…”
Section: Introductionmentioning
confidence: 99%
“…As refractive index n = √ µ, the structured zero-index medium can be realized by making its effective permittivity and/or effective permeability approach zero at the frequency of interest. Enoch et al [6] demonstrated that radiation beam of a source embedded in MTM will be refracted in a direction very close to the normal when the refractive index (n) is close to zero, in some frequency bands. Furthermore, epsilon-near-zero (ENZ) or mu-near-zero (MNZ) may show other interesting features such as the efficiency enhancement of a waveguide [8], and the transparent media and transmission enhancements [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation